Evaluation of labels and physical-chemical characterization of Kombuchas sold in the city of Duque de Caxias - RJ (Research, Society and Development, 2022)
Kombucha is a naturally fermented beverage that has been gaining prominence in the beverage industry. Due to their slightly acidic, bitter and gassy taste, these teas have been placed by many as an alternative to traditional carbonated drinks, especially by those looking for a more natural, healthy drink, with little sugar, without additives and dyes traditionally used. in the preparation of soft drinks. Despite being a millenary drink widely known in Asia, in Brazil it is still a little known and widespread drink. The objective of this work was to analyze physicochemically these drinks of the same flavor and from different batches and brands, to verify the possible uniformity and characteristics of these products. Methodology: The samples were acquired in the municipality of Duque de Caxias-RJ and the labeling parameters, pH, titratable acidity, alcohol content, antioxidants, color and presence of dyes were analyzed. Results and discussion: From the physical-chemical point of view, all samples were within the recommended by the legislation, however, with regard to labeling, several samples had allegations and words prohibited by the provisions of the Normative Instruction. The K samples had the highest content of phenolic compounds among the samples, with an average value of 94.95 mg eq of gallic acid/100mL. Conclusion: The physical-chemical parameters and nutritional labeling were analyzed and the great need for standardization regarding the appearance of the product and greater inspection in relation to the labeling was perceived.